SANKSI PIDANA TERHADAP TINDAK PIDANA PENGANIAYAAN YANG MENGAKIBATKAN LUKA-LUKA: Studi Kasus No.62/ Pid.B/ 2021/ PN Kbu - Muhtadli (Legalita, 2020)
This research discusses the Criminal Sanctions for the Crime of Persecution That Causes Injury (Case Study No. 62/ Pid.B/2021/ PN Kbu), In line with the improvement of science and technology in Lampung, economic activities have become more advanced, seen from the aspect of variety or intensity, more developed humans are also capable of carrying out criminal acts. A criminal act is an evil that everything has been determined in the Criminal Code (KUHP). A criminal act is a treatment that is prevented by a prohibition law, followed by threats or punishments in the form of certain crimes, for those who commit the violation. Questions that can be taken from all chapters in this thesis are: The judge's legal considerations when determining the criminal decision No.62/Pid.B/2021/PN Kbu, namely Article 351 paragraph (1) of the Criminal Code regarding Persecution and its references are seen from the explanations of witnesses, explanations of the perpetrators and based on the facts that have been seen in the in the trial, and the judge's certainty, so the decision given in the case is imprisonment for 1 (one) year 8 (eight) months, determining the prison time that has been experienced by the suspect, all of which is due to the punishment given, determining that the perpetrator is still in prison. prisoner.